Induction motor load generator system using direct torque control method - Mazhari, I.; Vahedi, A.; Masoum, Mohammad (Curtin University of Technoklogy, 2007)
Implementation of complicated tests for electrical machines usually demands special experimental setups and equipments. Getting to this target, electrical machine test benches are designed and constructed. In this paper, a direct torque controlled (DTC) load generator based on space vector modulation is proposed. To realize system performance with DTC method, classical DTC has been analyzed and is used for modelling the dynamometer. The performance of proposed dynamometer is investigated by simulating different parts of the system in SIMULINK/MATLAB environment and results are presented for several industrial load profiles.